Editorial: Microplastics and nanoplastics in polar areas: Arctic, Antarctica, and the world’s glaciers - Corami, Fabiana; Iannilli, Valentina; Hallanger, Ingeborg G. (Frontiers in Marine Science, 2025)
Plastic particles are present in biotic and abiotic matrices; hence, plastic pollution is a global issue involving terrestrial and marine fauna and poses a threat to humans. Ocean circulation is a crucial vector of microplastics worldwide. Plastic pollution is among the significant threats to the ocean ecosystem. Studies and papers on plastic pollution in the oceans worldwide have been reported. However, the distribution, characterization, and abundance of micro- and nano plastics in the global ocean still need to be carefully investigated. Once plastics are present in the environment, they denature, degrade, and are more prone to fragmentation. It is well established that large plastic objects and macroplastics fragment into mesoplastics and large microplastics through photodegradation and weathering. Hence microplastics easily break up into fragments <100 µm (small microplastics, SMPs) or even into sub-micrometric particles, the nanoplastics. The small size of these SMPs and nanoplastics allows them to be ingested by different organisms according to their mouthparts’ size. Besides, this fragmentation will enable additives and plasticizers to be released into the environment, where they may pose a threat to biota throughout the trophic web in various ecosystems, e.g., from oceans and soils to glaciers. Micro- and nanoplastics (MNPs) can be transported over long distances, together with the other airborne particles. As a result of long-range transport and short-range transport, airborne MNPs can be carried from worldwide to mountain glaciers; from mid-latitudes, they can reach the very high and very low latitudes, i.e., the Arctic and Antarctica. Due to global climate change, warm ocean streams heavily affect the sea circulation in polar areas, carrying regulated and emerging pollutants, microplastics being among them. In this scenario, polar environments may be significantly enriched by MNPs carried by warmer ocean currents intruding into the polar oceans and those in atmospheric aerosol. MNPs may threaten the sea ice formation and enhance the melting of glaciers. The melting and disappearance of glaciers and the intrusion of warm currents into polar areas are also compounded by the thawing of permafrost, which can release pollutants, including MNPs. This Research Topic aims to study the interconnected pathways of MNPs that are paramount to understanding the global microplastic cycle and how climate change alters polar environments and the rest of the world. Furthermore, we aim to identify bioindicators in marine species, populations, and ecosystems, while acknowledging the interconnectedness of freshwater, terrestrial and atmospheric environments to the polar environment. Research on world glaciers will provide a comprehensive evaluation of the impacts of plastic pollution on the marine polar environment and biota, including impacts on humans.
Article Number: 1587557
Keywords: Antarktis; forurensning; isbreer; klimaendringer; mikroplast; miljøgifter; polarområdene; økologi; økosystemer

Spatial Variations of Atmospheric Alkylated Polycyclic Aromatic Hydrocarbons across the Western Pacific to the Southern Ocean: Unexpected Increasing Deposition - Zhu, Fu-Jie; Lu, Xi-Mei; Jia, Jing-Wen; Zhang, Xue; Xing, De-Feng; Cai, Ming-Hong; Kallenborn, Roland; Li, Yi-Fan; Muir, Derek C. G.; Zhang, Zi-Feng; Zhang, Xianming (Environmental Science & Technology, 2025)
Spatial variations of atmospheric alkylated polycyclic aromatic hydrocarbons (Alk-PAHs) are key to understanding their long-range atmospheric transport (LRAT). However, limited Alk-PAHs data have hindered their LRAT characterizations on a global scale. In this study, 49 Alk-PAHs were measured in the atmospheric samples collected across the Western Pacific to the Southern Ocean. The summed concentration of 39 frequently detected Alk-PAHs (Σ39Alk-PAHs) was 25.8 ± 25.3 ng m–3. The concentrations of Σ39Alk-PAHs significantly declined with the decrease in latitude (°N). Higher concentrations (55.8 ± 33.8 ng m–3) were linked to continental air mass compared to oceanic/Antarctica air mass (17.0 ± 13.6 ng m–3), highlighting continental emissions as the primary source of marine atmospheric Alk-PAHs. An unexpected increase in the G/P partitioning ratio (KP) was found in samples farther away from the continent, which cannot be explained by the influence of temperature on the partitioning process. Deposition analysis suggested that gaseous concentrations and the G/P partitioning largely influenced deposition patterns. Hypothetical scenario analysis indicated that increased KP under snowy conditions could enhance the total Alk-PAH deposition. These findings emphasize the need for accurate characterization of partitioning and deposition processes when studying the global fate of Alk-PAHs, particularly in remote and polar regions.
Publisher: American Chemical Society
Keywords: Sørishavet; atmosfæren; biokjemi; forurensning; kjemi; miljøgifter

Microplastics in Southern Ocean sea ice: a pan-Antarctic perspective - Anna Kelly; Thomas Rodemann; Klaus M. Meiners; Heidi J. Auman; Sebastien Moreau; Francois Fripiat; Bruno Dellile; Delphine Lannuzel (Water Emerging Contaminants & Nanoplastics, 2024)
Microplastic (MP; plastic particles < 5 mm) pollution is pervasive in the marine environment, including remote polar environments. This study provides the first pan-Antarctic survey of MP pollution in Southern Ocean sea ice by analyzing sea ice cores from several diverse Antarctic regions. Abundance, chemical composition, and particle size data were obtained from 19 archived ice core samples. The cores were melted, filtered, and chemically analyzed using Fourier-transform infrared spectroscopy and 4,090 MP particles were identified. Nineteen polymer types were found across all samples, with an average concentration of 44.8 (± 50.9) particles·L-1. Abundance and composition varied with ice type and geographical location. Pack ice exhibited significantly higher particle concentrations than landfast ice, suggesting open ocean sources of pollution. Winter sea ice cores had significantly more MPs than spring and summer-drilled cores, suggesting ice formation processes play a role in particle incorporation. Smaller particles dominated across samples. Polyethylene (PE) and polypropylene (PP) were the most common polymers, mirroring those most identified across marine habitats. Higher average MP concentrations in developing sea ice during autumn and winter, contrasting lower levels observed in spring and summer, suggest turbulent conditions and faster growth rates are likely responsible for the increased incorporation of particles. Southern Ocean MP contamination likely stems from both local and distant sources. However, the circulation of deep waters and long-range transport likely contribute to the accumulation of MPs in regional gyres, coastlines, and their eventual incorporation into sea ice. Additionally, seasonal sea ice variations likely influence regional polymer compositions, reflecting the MP composition of the underlying waters.
Keywords: Sørishavet; forurensning; havis; iskjerner; mikroplast; sjøis

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Plastic occurrence, sources, and impacts in Antarctic environment and biota - Caruso, Gabriella; Bergami, Elisa; Singh, Neelu; Corsi, Ilaria (Water Biology and Security, 2022)
Several studies have documented that plastic pollution is affecting one of the most remote and pristine regions of our planet, Antarctica. Plastics of different size and polymeric composition have been retrieved in Antarctic sea ice, surface waters and sediments, with microplastics (mostly fibers) found both in terrestrial and marine organisms. Such evidence raises concerns about potential detrimental effects on biodiversity and ecosystem functions. The present review aims to report the most up-to-date knowledge on occurrence and distribution of plastic pollution in the Antarctic environment and biota including interaction with microorganisms, potential sources, and its impact on Antarctic biota. Our understanding of plastic pollution in this polar region will help us define the human footprint in Antarctica and predict future ecological risks.
Keywords: Sørishavet; forurensning; plastpartikler; økotoksikologi

Aerosol optical properties calculated from size distributions, filter samples and absorption photometer data at Dome C, Antarctica, and their relationships with seasonal cycles of sources - Virkkula, A.; Grythe, H.; Backman, J.; Petäjä, T.; Busetto, M.; Lanconelli, C.; Lupi, A.; Becagli, S.; Traversi, R.; Severi, M.; Vitale, V.; Sheridan, P.; et al. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; atmosfæren; forurensning

The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Publisher: Cambridge University Press
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

Trophic and fitness correlates of mercury and organochlorine compound residues in egg-laying Antarctic petrels - Carravieri, Alice; Warner, Nicholas A; Herzke, Dorte; Brault-Favrou, Maud; Tarroux, Arnaud; Fort, Jérôme; Bustamante, Paco; Descamps, Sébastien (Environmental Research, 2021)
Understanding the drivers and effects of exposure to contaminants such as mercury (Hg) and organochlorine compounds (OCs) in Antarctic wildlife is still limited. Yet, Hg and OCs have known physiological and fitness effects in animals, with consequences on their populations. Here we measured total Hg (a proxy of methyl-Hg) in blood cells and feathers, and 12 OCs (seven polychlorinated biphenyls, PCBs, and five organochlorine pesticides, OCPs) in plasma of 30 breeding female Antarctic petrels Thalassoica antarctica from one of the largest colonies in Antarctica (Svarthamaren, Dronning Maud Land). This colony is declining and there is poor documentation on the potential role played by contaminants on individual physiology and fitness. Carbon (δ13C) and nitrogen (δ15N) stable isotope values measured in the females' blood cells and feathers served as proxies of their feeding ecology during the pre-laying (austral spring) and moulting (winter) periods, respectively. We document feather Hg concentrations (mean ± SD, 2.41 ± 0.83 μg g−1 dry weight, dw) for the first time in this species. Blood cell Hg concentrations (1.38 ± 0.43 μg g−1 dw) were almost twice as high as those reported in a recent study, and increased with pre-laying trophic position (blood cell δ15N). Moulting trophic ecology did not predict blood Hg concentrations. PCB concentrations were very low (Σ7PCBs, 0.35 ± 0.31 ng g−1 wet weight, ww). Among OCPs, HCB (1.02 ± 0.36 ng g−1 ww) and p, p’-DDE (1.02 ± 1.49 ng g−1 ww) residues were comparable to those of ecologically-similar polar seabirds, while Mirex residues (0.72 ± 0.35 ng g−1 ww) were higher. PCB and OCP concentrations showed no clear relationship with pre-laying or moulting feeding ecology, indicating that other factors overcome dietary drivers. OC residues were inversely related to body condition, suggesting stronger release of OCs into the circulation of egg-laying females upon depletion of their lipid reserves. Egg volume, hatching success, chick body condition and survival were not related to maternal Hg or OC concentrations. Legacy contaminant exposure does not seem to represent a threat for the breeding fraction of this population over the short term. Yet, exposure to contaminants, especially Mirex, and other concurring environmental stressors should be monitored over the long-term in this declining population.
Keywords: Dronning Maud Land; forurensning; miljøendringer; miljøgifter; ornitologi; petreller; sjøfugler

Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

Persistent Organic Pollutants in the East Antarctic Atmosphere: Inter-Annual Observations from 2010 to 2015 Using High-Flow-Through Passive Sampling - Bengtson Nash, Susan M; Wild, Sean J; Hawker, Darryl W; Cropp, Roger A; Hung, Hayley; Wania, Frank; Xiao, Hang; Bohlin-Nizzetto, Pernilla; Bignert, Anders; Broomhall, Sara (Environmental Science & Technology, 2017)
In the first multiyear sampling effort for POPs in the eastern Antarctic atmosphere, 32 PCBs and 38 organochlorine pesticides were targeted in air collected with a high-flow-through passive sampler. Agricultural chemicals were found to dominate atmospheric profiles, in particular HCB and endosulfan-I, with average concentrations of 12 600 and 550 fg/m3, respectively. HCB showed higher concentrations in the austral summer, indicative of local, temperature-dependent volatilisation, while endosulfan-I appeared to show fresh, late-austral-summer input followed by temporally decreasing levels throughout the year. The current-use herbicide, trifluralin, and the legacy pesticides mirex and toxaphene, were detected in Antarctic air for the first time. Trifluralin was observed at low but increasing levels over the five-year period. Its detection in the Antarctic atmosphere provides evidence of its persistence and long-range environmental transport capability. While a time frame of five years exceeds the duration of most Antarctic air monitoring efforts, it is projected that continuous monitoring at the decadal scale is required to detect an annual 10% change in atmospheric concentrations of key analytes. This finding emphasizes the importance of continuous, long-term monitoring efforts in polar regions, that serve a special role as sentinel environments of hemispheric chemical usage trends.
Publisher: American Chemical Society
Keywords: Antarktis; atmosfæren; forurensning; kjemiske analyser; miljøgifter

Microplastic in the surface waters of the Ross Sea (Antarctica): Occurrence, distribution and characterization by FTIR - Cincinelli, Alessandra; Scopetani, Costanza; Chelazzi, David; Lombardini, Emilia; Martellini, Tania; Katsoyiannis, Athanasios; Fossi, Maria Cristina; Corsolini, Simonetta (Chemosphere, 2017)
This is the first survey to investigate the occurrence and extent of microplastic (MPs) contamination in sub surface waters collected near-shore and off-shore the coastal area of the Ross Sea (Antarctica). Moreover, a non-invasive method to analyze MPs, consisting in filtration after water sampling and analysis of the dried filter through Fourier Transform Infrared Spectroscopy (FTIR) 2D Imaging, using an FPA detector, was proposed. The non-invasiveness of analytical set-up reduces potential bias and allows subsequent analysis of the filter sample for determination of other classes of contaminants. MPs ranged from 0.0032 to 1.18 particle per m3 of seawater, with a mean value of 0.17 ± 0.34 particle m−3, showing concentrations lower than those found in the oceans worldwide. MPs included fragments (mean 71.9 ± 21.6%), fibers (mean 12.7 ± 14.3%), and others (mean 15.4 ± 12.8%). The presence of different types of MPs was confirmed by FTIR spectroscopy, with predominant abundance of polyethylene and polypropylene. The potential environmental impact arising from scientific activities, such as marine activities for scientific purposes, and from the sewage treatment plant, was also evidenced.
Keywords: Rosshavet; Sørishavet; forurensning; mikroplast; miljøgifter

On-site and in situ remediation technologies applicable to petroleum hydrocarbon contaminated sites in the Antarctic and Arctic - Camenzuli, Danielle; Freidman, Benjamin L (Polar Research, 2015)
Petroleum hydrocarbon contaminated sites, associated with the contemporary and legacy effects of human activities, remain a serious environmental problem in the Antarctic and Arctic. The management of contaminated sites in these regions is often confounded by the logistical, environmental, legislative and financial challenges associated with operating in polar environments. In response to the need for efficient and safe methods for managing contaminated sites, several technologies have been adapted for on-site or in situ application in these regions. This article reviews six technologies which are currently being adapted or developed for the remediation of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Bioremediation, landfarming, biopiles, phytoremediation, electrokinetic remediation and permeable reactive barriers are reviewed and discussed with respect to their advantages, limitations and potential for the long-term management of soil and groundwater contaminated with petroleum hydrocarbons in the Antarctic and Arctic. Although these technologies demonstrate potential for application in the Antarctic and Arctic, their effectiveness is dependent on site-specific factors including terrain, soil moisture and temperature, freeze–thaw processes and the indigenous microbial population. The importance of detailed site assessment prior to on-site or in situ implementation is emphasized, and it is argued that coupling of technologies represents one strategy for effective, long-term management of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Keywords: Petroleum hydrocarbons; remediation; Antarctica; Arctic; cold regions; contaminated site.
Keywords: Antarktis; forurensning; hydrokarboner; miljøvern; petroleum; polarområdene

Polychlorinated biphenyl exposure and corticosterone levels in seven polar seabird species - Tartu, Sabrina; Angelier, Frédéric; Bustnes, Jan-Ove; Moe, Børge; Hanssen, Sven Are; Herzke, Dorte; Gabrielsen, Geir Wing; Verboven, Nanette; Verreault, J; Labadie, Pierre; Budzinski, Helene; Wingfield, John C; et al. (Environmental Pollution, 2015)
The role of polychlorinated biphenyls (PCBs) on exposure-related endocrine effects has been poorly investigated in wild birds. This is the case for stress hormones including corticosterone (CORT). Some studies have suggested that environmental exposure to PCBs and altered CORT secretion might be associated. Here we investigated the relationships between blood PCB concentrations and circulating CORT levels in seven free-ranging polar seabird species occupying different trophic positions, and hence covering a wide range of PCB exposure. Blood ∑7PCB concentrations (range: 61–115,632 ng/g lw) were positively associated to baseline or stress-induced CORT levels in three species and negatively associated to stress-induced CORT levels in one species. Global analysis suggests that in males, baseline CORT levels generally increase with increasing blood ∑7PCB concentrations, whereas stress-induced CORT levels decrease when reaching high blood ∑7PCB concentrations. This study suggests that the nature of the PCB-CORT relationships may depend on the level of PCB exposure.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; polarområdene; sjøfugler; stresshormoner; zoologi

Corticosterone, prolactin and egg neglect behavior in relation to mercury and legacy POPs in a long-lived Antarctic bird - Tartu, Sabrina; Angelier, Frédéric; Wingfield, John C; Bustamante, Paco; Labadie, Pierre; Budzinski, Helene; Weimerskirch, Henri; Bustnes, Jan-Ove; Chastel, Olivier (Science of the Total Environment, 2015)
Seabirds often have high loads of contaminants. These contaminants have endocrine disrupting properties but their relationships with some endocrine mechanisms are still poorly investigated in free-living organisms. This is the case for the stress response which shifts energy investment away from reproduction and redirects it towards survival. In birds, this stress response is achieved through a release of corticosterone and is also accompanied by a decrease in circulating prolactin, an anterior pituitary hormone widely involved in regulating parental cares. We measured blood concentrations of some legacy persistent organic pollutants (POPs) and mercury (Hg) and examined their relationships with the corticosterone and prolactin responses of known-age (9–46years old) incubating snow petrels (Pagodroma nivea) to a standardized capture/handling stress protocol. In this Antarctic seabird, we also investigated whether high contaminant burden correlates with a higher occurrence of egg neglect, a frequently observed behavior in snow petrels. POPs and Hg were unrelated to age. Stress-induced corticosterone concentrations were positively related to POPs in both sexes, and stress-induced prolactin concentrations were negatively related to Hg in males. Egg-neglect behavior was not related to POPs burden, but males with higher Hg concentrations were more likely to neglect their egg. This suggests that in birds, relationships between age and contaminants are complex and that even low to moderate concentrations of POPs and Hg are significantly related to hormonal secretion. In this Antarctic species, exposure to legacy POPs and Hg could make individuals more susceptible to environmental stressors such as ongoing disturbances in Polar Regions.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; petreller; polarområdene; reproduksjon; sjøfugler; zoologi

Comment on “Unexpected Occurrence of Volatile Dimethylsiloxanes in Antarctic Soils, Vegetation, Phytoplankton, and Krill” - Warner, Nicholas A; Krogseth, Ingjerd S; Whelan, Mick J (Environmental Science & Technology, 2015)
Sanchís et al. (2015) recently reported the occurrence of volatile methyl siloxanes (VMS) in soil, vegetation, phytoplankton, and krill samples from Antarctica. As the paper’s title suggests, findings of these chemicals in such a remote region is unexpected and of significant concern. However, our experience with the analysis of these compounds at trace concentrations suggests that the observations reported may have been influenced by artifacts. Here we present our concerns based upon known emissions, physicochemical properties and on apparent quality control measures including treatment of blank samples and detection limits.
Publisher: American Chemical Society
Keywords: Antarktis; forurensning; miljøgifter

An Antarctic Research Station as a Source of Brominated and Perfluorinated Persistent Organic Pollutants to the Local Environment - Wild, Seanan; McLagan, David; Schlabach, Martin; Bossi, Rossana; Hawker, Darryl; Cropp, Roger; King, Catherine K; Stark, Jonathan S; Mondon, Julie; Nash, Susan Bengtson (Environmental Science & Technology, 2015)
This study investigated the role of a permanently manned Australian Antarctic research station (Casey Station) as a source of contemporary persistent organic pollutants (POPs) to the local environment. Polybrominated diphenyl ethers (PBDEs) and poly- and perfluoroalkylated substances (PFASs) were found in indoor dust and treated wastewater effluent of the station. PBDE (e.g., BDE-209 26–820 ng g–1 dry weight (dw)) and PFAS levels (e.g., PFOS 3.8–2400 ng g–1 (dw)) in dust were consistent with those previously reported in homes and offices from Australia, reflecting consumer products and materials of the host nation. The levels of PBDEs and PFASs in wastewater (e.g., BDE-209 71–400 ng L–1) were in the upper range of concentrations reported for secondary treatment plants in other parts of the world. The chemical profiles of some PFAS samples were, however, different from domestic profiles. Dispersal of chemicals into the immediate marine and terrestrial environments was investigated by analysis of abiotic and biotic matrices. Analytes showed decreasing concentrations with increasing distance from the station. This study provides the first evidence of PFAS input to Polar regions via local research stations and demonstrates the introduction of POPs recently listed under the Stockholm Convention into the Antarctic environment through local human activities.
Publisher: American Chemical Society
Keywords: Antarktis; forskningsstasjoner; forurensning; menneskelig påvirkning; miljøgifter

HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

A Nutritional-Toxicological Assessment of Antarctic Krill Oil versus Fish Oil Dietary Supplements - Bengtson Nash, Susan M; Schlabach, Martin; Nichols, Peter D (Nutrients, 2014)
Fish oil dietary supplements and complementary medicines are pitched to play a role of increasing strategic importance in meeting daily requirements of essential nutrients, such as long-chain (≥C20, LC) omega-3 polyunsaturated fatty acids and vitamin D. Recently a new product category, derived from Antarctic krill, has been launched on the omega-3 nutriceutical market. Antarctic krill oil is marketed as demonstrating a greater ease of absorption due to higher phospholipid content, as being sourced through sustainable fisheries and being free of toxins and pollutants; however, limited data is available on the latter component. Persistent Organic Pollutants (POP) encompass a range of toxic, man-made contaminants that accumulate preferentially in marine ecosystems and in the lipid reserves of organisms. Extraction and concentration of fish oils therefore represents an inherent nutritional-toxicological conflict. This study aimed to provide the first quantitative comparison of the nutritional (EPA and DHA) versus the toxicological profiles of Antarctic krill oil products, relative to various fish oil categories available on the Australian market. Krill oil products were found to adhere closely to EPA and DHA manufacturer specifications and overall were ranked as containing intermediate levels of POP contaminants when compared to the other products analysed. Monitoring of the pollutant content of fish and krill oil products will become increasingly important with expanding regulatory specifications for chemical thresholds.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; miljøgifter; plankton; toksikologi

Annual cycle of Antarctic baseline aerosol: controlled by photooxidation-limited aerosol formation - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Stohl, Andreas; Thompson, Rona L (Atmospheric Chemistry and Physics (Print), 2014)
This article investigates the annual cycle observed in the Antarctic baseline aerosol scattering coefficient, total particle number concentration, and particle number size distribution (PNSD), as measured at Troll Atmospheric Observatory. Mie theory shows that the annual cycles in microphysical and optical aerosol properties have a common cause. By comparison with observations at other Antarctic stations, it is shown that the annual cycle is not a local phenomenon, but common to central Antarctic baseline air masses. Observations of ground-level ozone at Troll as well as backward plume calculations for the air masses arriving at Troll demonstrate that the baseline air masses originate from the free troposphere and lower stratosphere region, and descend over the central Antarctic continent. The Antarctic summer PNSD is dominated by particles with diameters <100 nm recently formed from the gas-phase despite the absence of external sources of condensible gases. The total particle volume in Antarctic baseline aerosol is linearly correlated with the integral insolation the aerosol received on its transport pathway, and the photooxidative production of particle volume is mostly limited by photooxidative capacity, not availability of aerosol precursor gases. The photooxidative particle volume formation rate in central Antarctic baseline air is quantified to 207 ±4 μm3/(MJ m). Further research is proposed to investigate the applicability of this number to other atmospheric reservoirs, and to use the observed annual cycle in Antarctic baseline aerosol properties as a benchmark for the representation of natural atmospheric aerosol processes in climate models.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; klimamodeller; miljøgifter

Age-Related Mercury Contamination and Relationship with Luteinizing Hormone in a Long-Lived Antarctic Bird - Tartu, Sabrina; Bustamante, Paco; Goutte, Aurélie; Cherel, Yves; Weimerskirch, Henri; Bustnes, Jan Ove; Chastel, Olivier (PloS One, 2014)
Seabirds, as long-lived top predators, accumulate contaminants such as mercury (Hg), an established endocrine disruptor. In long lived species hormonal secretion varies with age; therefore, Hg-induced endocrine disruption may be exacerbated in some age classes. Here we investigated relationships between blood total Hg and luteinizing hormone (LH, a key pituitary hormone for the onset of breeding), in pre-laying known-age (11–45 years old) snow petrels (Pagodroma nivea) from Adélie Land, Antarctica. We predicted that 1) blood Hg would increase with advancing age as a consequence of bio-accumulation; and that 2) increasing blood Hg would be related to decreased concentrations of LH in the most Hg-contaminated individuals. Hg concentrations were higher in females than in males (p<0.001), and contrary to our prediction, decreased with advancing age in males (p = 0.009) and tended to do so in females (p = 0.06). The analysis of stable isotopes (δ13C and δ15N) suggested that this unexpected pattern could originate from age and sex-related variations in trophic niche, and hence Hg exposure. Regarding LH, our prediction was only supported in young birds (≤23 years) where baseline LH was inversely correlated with Hg concentrations (p = 0.04). Hg burden did not predict baseline LH or GnRH-induced LH in birds that were more than 23 years old. These results show that age and contaminants may interfere with major endocrine mechanisms and, together with other recent studies, support the view that Hg could be connected to LH secretion and could then impair the fitness of long-lived birds.
Publisher: Public Library of Science
Keywords: Antarktis; forurensning; kjemiske analyser; miljø; nevrobiologi; ornitologi; petreller; sjøfugler; stabile isotoper; zoologi; økologiske nisjer

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Long-term monitoring of persistent organic pollutants (POPs) at the Norwegian Troll station in Dronning Maud Land, Antarctica - Kallenborn, Roland; Breivik, Knut; Eckhardt, Sabine; Lunder, C R; Manø, S; Schlabach, Martin; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2013)
A first long-term monitoring of selected persistent organic pollutants (POPs) in Antarctic air has been conducted at the Norwegian research station Troll (Dronning Maud Land). As target contaminants 32 PCB congeners, α- and γ-hexachlorocyclohexane (HCH), trans- and cis-chlordane, trans- and cis-nonachlor, p,p'- and o,p-DDT, DDD, DDE as well as hexachlorobenzene (HCB) were selected. The monitoring program with weekly samples taken during the period 2007–2010 was coordinated with the parallel program at the Norwegian Arctic monitoring site (Zeppelin mountain, Ny-Ålesund, Svalbard) in terms of priority compounds, sampling schedule as well as analytical methods. The POP concentration levels found in Antarctica were considerably lower than Arctic atmospheric background concentrations. Similar to observations for Arctic samples, HCB is the predominant POP compound, with levels of around 22 pg m−3 throughout the entire monitoring period. In general, the following concentration distribution was found for the Troll samples analyzed: HCB > Sum HCH > Sum PCB > Sum DDT > Sum chlordanes. Atmospheric long-range transport was identified as a major contamination source for POPs in Antarctic environments. Several long-range transport events with elevated levels of pesticides and/or compounds with industrial sources were identified based on retroplume calculations with a Lagrangian particle dispersion model (FLEXPART).
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; miljøovervåking

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Publisher: American Chemical Society
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Atmospheric mercury observations from Antarctica: seasonal variation and source and sink region calculations - Pfaffhuber, Katrine Aspmo; Berg, Torunn; Hirdman, D; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2012)
Long term atmospheric mercury measurements in the Southern Hemisphere are scarce and in Antarctica completely absent. Recent studies have shown that the Antarctic continent plays an important role in the global mercury cycle. Therefore, long term measurements of gaseous elemental mercury (GEM) were initiated at the Norwegian Antarctic Research Station, Troll (TRS) in order to improve our understanding of atmospheric transport, transformation and removal processes of GEM. GEM measurements started in February 2007 and are still ongoing, and this paper presents results from the first four years. The mean annual GEM concentration of 0.93 ± 0.19 ng m−3 is in good agreement with other recent southern-hemispheric measurements. Measurements of GEM were combined with the output of the Lagrangian particle dispersion model FLEXPART, for a statistical analysis of GEM source and sink regions. It was found that the ocean is a source of GEM to TRS year round, especially in summer and fall. On time scales of up to 20 days, there is little direct transport of GEM to TRS from Southern Hemisphere continents, but sources there are important for determining the overall GEM load in the Southern Hemisphere and for the mean GEM concentration at TRS. Further, the sea ice and marginal ice zones are GEM sinks in spring as also seen in the Arctic, but the Antarctic oceanic sink seems weaker. Contrary to the Arctic, a strong summer time GEM sink was found, when air originates from the Antarctic plateau, which shows that the summertime removal mechanism of GEM is completely different and is caused by other chemical processes than the springtime atmospheric mercury depletion events. The results were corroborated by an analysis of ozone source and sink regions.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; ozonlaget

Foreword: The complex business of managing human activities and protecting the environment of the polar regions - Tin, Tina; Liggett, Daniela; Maher, Patrick T (Polar Research, 2012)
The thematic cluster ‘‘Human impacts in the Arctic and Antarctic’’ in Polar Research has its origins in the International Polar Year (2007-09) Oslo Science Conference held in Oslo, Norway, from 8 to 12 June 2010. We were the co-convenors of the session ‘‘Human impacts in the Arctic and Antarctic: regulatory and management implications,’’ in which 27 talks and 21 posters were presented over the course of two days. We invited contributors to the conference session to explore all types of impacts of human activities and regional environmental change in the polar regions, with a special focus on highlighting the management priorities for the protection of the landscape (environment and people) of the polar regions in the face of increasing human activity. Exploring a wide range of topics ranging from human wildlife interactions to chemical contamination and from whaling to polar tourism, contributors provided examples of existing environmental management regimes that are working as well as those that are not.
Keywords: Antarktis; forurensning; menneskelig påvirkning; miljøvern; polarområdene; turisme; økosystemer

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

Atmospheric monitoring at the Norwegian Antarctic station Troll: measurement programme and first results - Hansen, Georg; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Krognes, Terje; Lunder, Chris; Stebel, Kersten; Schmidbauer, Norbert; Solberg, Sverre; Yttri, Karl Espen (Polar Research, 2009)
The Troll Atmospheric Station in Antarctica (72°01'S, 2°32'E, 1309 m a.s.l.) was established and put into operation in early 2007. The main foci of the measurement programme are pollution and aerosols in the transition zone between the coastal zone and the inland ice plateau, complementing existing observation programmes along the Antarctic coast and on the Antarctic Plateau. After one year of operation, the monitoring programme is fully operative, and a comprehensive set of data is being analysed. As far as comparable data are available, there is satisfactory agreement between previous and new data. Both aerosol data and measurements of pollution indicate the episodic influence of coastal air masses throughout the year. Background values of medium long-lived pollutants such as CO, O3 and Hg are up to 50% lower than at corresponding Arctic sites (depending on the season), but are still significant. Total ozone and UV doses manifest the recurring Antarctic stratospheric ozone hole, which was moderately severe, but very persistent in 2007. Specific episodes of elevated aerosol concentration and mercury activation are currently under detailed investigation, and will be published separately.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; meteorologi; målinger; ozonlaget

Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

Reproductive performance and organochlorine pollutants in an Antarctic marine top predator: The south polar skua - Bustnes, Jan O; Tveraa, Torkild; Varpe, Øystein; Henden, John A; Skaare, Janneche U (Environment International, 2007)
Keywords: Dronning Maud Land; forurensning; miljø; ornitologi; polarområdene; reproduksjon; økologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Metal dynamics in an Antarctic food chain - Nygård, Torgeir; Lie, Elisabeth; Røv, Nils; Steinnes, Eiliv (Marine Pollution Bulletin, 2001)
The concentrations of copper, zinc, cadmium, selenium and mercury were determined in eggs, muscle, liver, kidney and stomach content of nestlings and adults of the Antarctic petrel, Thalassoica antarctica, and its predator, the south polar skua, Chataracta maccormicki, from Svarthamaren, Dronning Maud Land, Antarctica. The dominant food of the petrels is krill, Euphausia superba. The results show relatively high levels of cadmium in krill, which is assumed to be the main reason for the high levels of cadmium in petrels and skuas. Cadmium is almost absent in eggs, but accumulates very rapidly with age in nestlings. The copper concentrations in livers of nestling petrels reach very high levels during growth. This may be seen in connection with physiological development processes. Mercury seems to be accumulated with age and between trophic levels. Among the nestlings, the mercury levels decrease with increasing age, which may be accomplished by the excretion of mercury through the growth of feathers and as a dilution effect during growth. Selenium and mercury are inversely correlated in nestlings. The levels of zinc were similar for different nestling stages and between nestlings and adults in skuas and petrels.
Keywords: Dronning Maud Land; antarktispetrell; forurensning; fugler; krill; miljøgifter; næringskjede; ornitologi

Determination of Q1, an unknown organochlorine contaminant, in human milk, Antarctic air, and further environmental samples - Vetter, Walter; Alder, Lutz; Kallenborn, Roland; Schlabach, Martin (Environmental Pollution, 2000)
Q1, an organochlorine component with the molecular formula C(9)H(3)Cl(7)N(2) and of unknown origin was recently identified in seal blubber samples from the Namibian coast (southwest of Africa) and the Antarctic. In these samples, Q1 was more abundant than PCBs and on the level of DDT residues. Furthermore, Q1 was more abundant in seals from the Antarctic than the Arctic. To prove this assumption, gas chromatography-electron-capture negative ion mass spectrometry (GC/ECNI-MS), which is sensitive and selective for Q1, allowed for screening of traces of Q1 even in samples with particularly high levels of other organochlorine contaminants. Q1 was isolated by high-performance liquid chromatography (HPLC) from a skua liver sample. A 1:1 mixture with trans-nonachlor in electron-capture detectors (ECDs) was used to determine the relative response factor with ECNI-MS. The ECNI-MS response of Q1 turned out to be 4.5 times higher than that of trans-nonachlor in an ECD. With GC/ECNI-MS in the selected ion-monitoring mode, four Antarctic and four Arctic air samples were investigated for the presence of Q1. In the Antarctic air samples, Q1 levels ranged from 0.7 to 0.9 fg/m(3). In Arctic air samples, however, Q1 was below the detection limit (<0.06 fg/m(3) or 60 ag/m(3)). We also report on high Q1 levels in selected human milk samples (12-230 microg/kg lipid) and, therefore, suggested that the unknown Q1 is an environmental compound whose origin and distribution should be investigated in detail. Our data confirm that Q1 is a bioaccumulative natural organochlorine product. Detection of a highly chlorinated natural organochlorine compound in air and human milk is novel.
Keywords: Antarktis; forurensning; kromatografi; miljøgifter; miljøovervåking; toksikologi

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Publisher: [Springer, Royal Swedish Academy of Sciences]
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Publisher: [Springer, Royal Swedish Academy of Sciences]
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton

Levels and interactions of heavy metals in sea birds from Svalbard and the Antarctic - Norheim, Gunnar (Environmental Pollution (Barking, Essex: 1987), 1987)
Samples of liver and kidney from 92 seabirds of ten species collected on Spitsbergen and in the Antarctic, were analysed for their content of copper, zinc, cadmium, lead, mercury and selenium. Significantly higher levels of copper and zinc were observed in birds from Spitsbergen than in those from the Antarctic, while the opposite was true for selenium. The highest cadmium levels were found in fulmar Fulmarus glacialis and macaroni penguin Eudyptes chrysolophus. A possibility of kidney damage due to cadmium exists. The highest mercury levels were recorded in brown skua Catharacta lonnbergi collected at Bouvetøya. Lead was not detected in any of the birds. Significant correlations were observed between levels of several of the metals studied, especially between cadminum and zinc and between mercury and selenium. However, for all birds, the highest correlation coefficients were observed when the molar concentrations of cadmium plus mercury, and selenium plus zinc, were used in the calculations. Thus several protective mechanisms may operate to diminish effects of heavy metal contaminants.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; NARE 1978/79; forurensning; fugler; miljøgifter; ornitologi

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica) - Soevik, Torleif; Braekkan, Olaf R. (Journal of the Fisheries Research Board of Canada, 1979)
Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Key words: krill, red feed, deep sea prawn, fluoride.
Keywords: Sørishavet; biokjemi; forurensning; krill; marin biologi; miljøgifter; plankton

Forurensing av polarområdene? Et spørsmål om regulering av utviklingen - Sollie, Finn (Internasjonal politikk, 1972)
Keywords: Antarktis; Antarktistraktaten; forurensning; internasjonal; miljø; politikk; økologi